¿Por qué surgen las crisis monetarias y cómo podrían evitarse? - Económicas, Cuestiones (2001)
This article deals with different factors and phases that may influence or cause a currency crisis. Many emerging countries have introduced a peg vis-á-vis a reserve currency (c.g. the US dollar) in order to stabilize them economies añter a period of high inflation, low ceonumic growth or persistont budget - and current account deficits. In order to attract foreign capital, domestic markcts were liberalized.Excessive credit ercation and increasing debts of domestic firms and banks in foreign currency led to high risk exposure which in turn gave risc to adverse selection and moral hazard problems. The lack of bank supervision and risk management rules, together with corruption and nepotism, made such countries vulnerable to real estate bubbles and banking crises. The high amount of short-term capital inflow increased volatility, that, in view of rising uncertainty, caused substantial losses of foreign currency reserves of the central bank and finally led to abandon the currency peg in spite of IMF credit programs. Contagion was also a driving clement in this context.